PENGGUNAAN MEDIA BIG BOOK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS II DI SDN 01 KOTAPINANG - Salmida Sima Aini Siagian; Mardianto Mardianto; Ramadan Lubis (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to determine how the use of Big Book media to improve the reading skills of grade II students at SDN 01 Kotapinang. This study uses a descriptive qualitative research method. The results of this study use observation data, interviews, tests and field notes. The results of test 1 obtained results using reading media obtained that there were 5 students whose scores were "Very Good", 4 students had scores "Good", 4 students had scores "Enough", then 3 students had scores "Less" and 5 students had scores with the results "Fail". The results of test 2 obtained results as many as 11 students who got scores with the category "very good", students who got scores with the category "good" as many as 7 students. Then students who got scores with the category "enough" as many as 2 students and students who got scores with the category "less" as many as 1 student and students who got scores with the category "fail" none. So the Big Book media is proven to be effective in improving students' reading skills.